Spontaneous and emergent extrapyramidal syndromes in Black Africans with first-episode schizophrenia and first exposure to antipsychotics (2021)
Background: Persons of African ancestry are thought to carry a higher risk for extrapyramidal syndromes (EPS) in schizophrenia. Aim: We investigated the phenomenon of spontaneous and treatment-emergent EPS in a sample comprising Xhosa (South Africa) and Yoruba (Nigeria) Africans with first-episode schizophrenia and first exposure to antipsychotics. Methods: The Extrapyramidal Symptom Rating Scale (ESRS) and a variety of validated tools were used for the assessment of participants before, and two-weekly after treatment with low dose flupenthixol decanoate. Participants were followed up for 12 months. Association of EPS with clinical characteristics was investigated using Pearson’s correlation and linear regression analyses. Results: Of 88 participants at baseline, 16 (18.1%) had at least one definite EPS prior to antipsychotic exposure and 34 (38.6%) had treatment-emergent EPS. While spontaneous Parkinsonism was associated with negative symptoms (r¼0.2, p¼0.043; b¼0.6, p¼0.043), treatment-emergent EPS demonstrated non-significant correlations with clinical characteristics. Apart from dyskinesia, the frequency of treatment-emergent EPS decreased over 12 months observation. Conclusion: These findings support the hypothesis suggesting that spontaneously occurring Parkinsonism in schizophrenia may be the motor spectrum of negative symptomatology. Future studies of this relationship may lead to early identification of patients who may be more sensitive to EPS.